2015
DOI: 10.1146/annurev-animal-022114-111038
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Design and Application of Enteric Viral Vaccines

Abstract: Enteric viral infections in domestic animals cause significant economic losses. The recent emergence of virulent enteric coronaviruses [porcine epidemic diarrhea virus (PEDV)] in North America and Asia, for which no vaccines are available, remains a challenge for the global swine industry. Vaccination strategies against rotavirus and coronavirus (transmissible gastroenteritis virus) infections are reviewed. These vaccination principles are applicable against emerging enteric infections such as PEDV. Maternal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
129
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 116 publications
(129 reference statements)
3
129
0
1
Order By: Relevance
“…Indeed, a so-called 'gut-mammary glands-sIgA axis' model was postulated more than 40 years ago to address how lactogenic immunity could control infection of TGEV, a close relative of PEDV (Bohl et al, 1972). According to this notion, natural infection or oral administration of live vaccines can induce IgA plasma cell precursors in Peyer's patches and mesenteric lymph nodes, giving rise to robust generation of IgA plasma cells that secrete pathogen-specific sIgA antibodies into the colostrum and milk (Chattha et al, 2015). Recently, proof of this concept was shown in a study by Goede et al (2015) in which 100 % of piglets (nw50) born to sows pre-exposed to a mild strain of PEDV could be protected from lethal challenge of the highly virulent strain.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a so-called 'gut-mammary glands-sIgA axis' model was postulated more than 40 years ago to address how lactogenic immunity could control infection of TGEV, a close relative of PEDV (Bohl et al, 1972). According to this notion, natural infection or oral administration of live vaccines can induce IgA plasma cell precursors in Peyer's patches and mesenteric lymph nodes, giving rise to robust generation of IgA plasma cells that secrete pathogen-specific sIgA antibodies into the colostrum and milk (Chattha et al, 2015). Recently, proof of this concept was shown in a study by Goede et al (2015) in which 100 % of piglets (nw50) born to sows pre-exposed to a mild strain of PEDV could be protected from lethal challenge of the highly virulent strain.…”
Section: Discussionmentioning
confidence: 99%
“…Acute infectious diarrhea is a major cause of high morbidity and mortality in piglets worldwide. Enteric infections in animals are frequently associated with viruses, including rotaviruses and CoVs (Chattha et al, 2015). A metagenomics analysis of diarrheic and healthy samples from China in 2012 found porcine CoVs in 77 % of the diarrheic samples, and only in around 7 % of the healthy samples, highlighting the potential importance of CoVs as enteric porcine pathogens (Zhang et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…The three enteric CoVs (TGEV, PEDV and PDCoV) infect mainly small intestinal villous enterocytes, causing acute necrosis that leads to villi atrophy (Chattha et al, 2015; Jung et al, 2015b; Jung and Saif, 2015; Jung et al, 2014). This could produce a severe diarrhea as a consequence of malabsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field, it has been observed that prior exposure of the sow herd to PEDV ameliorates the impact of PEDV infection in neonates, presumably via maternal immune mechanisms . Based on these observations, it has been postulated that PEDV-specific IgG and IgA in colostrum and milk are critical for the protection of neonatal piglets against PEDV (Chattha et al, 2015;Song et al, 2015). Using TGEV as a model, the assumption is that lactogenic immunity against PEDV is induced by enteric infection following oral exposure .…”
Section: Introductionmentioning
confidence: 99%